1980
DOI: 10.1111/j.1365-2044.1980.tb03885.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐infection from contaminated anaesthetic equipment

Abstract: SummaryA definite relationship between the use of contaminated anaesthetic equipment and subsequent pulmonary infection remains to be established. There is however indirect and circumstantial evidence suggesting that cross-infection may occur, and further an increased susceptibility of surgical patients to pulmonary infections has been demonstrated. Decontamination should be recommended bejore the equipment is re-used. Pasteurisation may protie sufficient and this can be obtained employing a specially designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 84 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…The filter was changed between cases by 7.2% of the respondents in the present study, but it is likely that, in the year since the study was undertaken, the use of bacterial filters has increased. It has been shown that anaesthetic breathing systems can become contaminated with organisms from the respiratory tract, especially with coughing [25–28]. It is recommended that either an appropriate filter should be placed between the patient and the breathing system, with a new filter being used for each patient, or that a new breathing system be used for each patient, especially in paediatric practice [3].…”
Section: Discussionmentioning
confidence: 99%
“…The filter was changed between cases by 7.2% of the respondents in the present study, but it is likely that, in the year since the study was undertaken, the use of bacterial filters has increased. It has been shown that anaesthetic breathing systems can become contaminated with organisms from the respiratory tract, especially with coughing [25–28]. It is recommended that either an appropriate filter should be placed between the patient and the breathing system, with a new filter being used for each patient, or that a new breathing system be used for each patient, especially in paediatric practice [3].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing awareness of the complexity of patients presenting for anaesthesia or ventilation in an intensive care environment is crucial to modern practice. Surgery is associated with alterations in cellmediated and humoral immunity 49,50 which may be accentuated by the clinical state of the patient and medications 41 . The use of oxygen at concentrations greater than 21% results in depression of alveolar macrophage function 26 .…”
Section: Anaesthetic Equipment As a Vector For Cross-infectionmentioning
confidence: 99%
“…There is a paucity of evidence involving other infective agents. However, as Nielson et al 41 conclude, most work indicates that cross-infection could occur, and that surgical patients have increased susceptibility to infection anyway. Given the lack of information about infection by viral agents it cannot be argued that the anaesthetic and breathing circuit pose a minimal infectious hazard to the patient.…”
Section: Anaesthetic Equipment As a Vector For Cross-infectionmentioning
confidence: 99%
“…They are usually made of corrugated semi-disposable plastic tubing, which makes them prone to the retention of micro-organisms (Murphy et al 1991). If pathogenic bacteria can survive in anaesthesia breathing systems, and if they can be eluted in the fresh gas flow, then the potential for cross-contamination exists (Nielsen et al 1980;Langevin et al 1999). Previous reports have stated that there is a risk of bacterial transmission through anaesthetic equipment (Phillips & Spencer 1965;Beck & Zadeh 1968;Olds et al 1972) but many failed to provide a proof of causation (Albrecht & Dryden 1974).…”
Section: Introductionmentioning
confidence: 99%